IMPLEMENTATION OF CLUSTERING ON TWEET UPLOADING SIDE EFFECTS OF COVID-19 POST VACCINATION USING K-MEANS ALGORITHM - Santi, Santi; Februariyanti, Herny (Informatika, Universitas Jenderal Soedirman, 2023)
The Covid-19 Vaccination Program has become pros and cons among Indonesian people including Twitter social media users. When the program was running, Twitter users started uploading tweets regarding the side effects that occurred, ranging from mild to severe, both scientifically proven. or not. Of all uploaded tweets, by applying text mining, only tweets containing the queries